(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The main factor in maintaining good performance for air pistol athletes is to keep a stable posture without physical change. In addition, the athletes are ought to implement various approaches to enhance their shooting performance. The athletes have attempted to use different shoes to keep their balance intact. The present study evaluated effects of different shoes on kinematics (leg joint angles) of 8 elite shooters while performing air gun shooting. The results suggested that there were no statistical differences in either leg angles. The results suggested that the shoes in the present study did not influence kinematic changes of a body while performing air gun shooting.